Entre encantament e desencantament : la Nimes contada de Jòrgi Gros - Philippe Gardy (Revue des Langues Romanes)
Georges (or Jòrgi) Gros is the author of a long-lasting Occitan work in which the tradition of the tale to be told and that of the novelistic autobiography, with different means, face the same difficulty: the passage from one era to another, throughout the 20th century. The central figure in this transformation is the city of Nîmes, whose form was profoundly altered at the same time as its historical language, Occitan, faded from its traditional strongholds. The strength and originality of Gros's work lie in its position, at the vanishing point between the loss of a past and the projection of a future, and in the literary aesthetic that this position gives rise to. A writing of opposites and contradictions that leads to the emergence of a very personal style, a kind of recalcitrant postmodernity.